Incidence of Tuberculosis in Systemic Necrotizing Vasculitides: A Population-Based Study From an Intermediate-Burden Country - Ahn, Sung Soo; Han, Minkyung; Yoo, Juyoung; Park, Yong-Beom; Jung, Inkyung; Lee, Sang-Won (Frontiers in Medicine, 2020)
Objective: Tuberculosis (TB) has a significant impact on public health; however, its incidence in patients with systemic necrotizing vasculitides (SNV) remains unknown. Therefore, we evaluated the incidence of TB in patients with SNV using a nationwide claims database. Methods: The Health Insurance and Review Agency database was used to identify patients diagnosed with SNV between 2010 and 2018. The standardized incidence ratio (SIR) was calculated to compared the risk of TB between patients and the general population, based on the 2016 annual national TB report. The incidence of TB after SNV diagnosis was compared by estimating age- and sex- adjusted incidence rate ratio (IRR). A time-dependent Cox regression analysis was performed to estimate factors associated with TB. Results: Among the included 2,660 patients, 51 (1.9%) developed TB during the follow-up period. The risk of TB was significantly higher in patients with SNV [SIR 6.09, 95% confidence interval (CI) 4.53–8.00], both in men (SIR 5.95) and women (SIR 6.26), than in the general population; this increased risk was consistent in all disease subtypes, except eosinophilic granulomatosis with polyangiitis. Additionally, the incidence of TB was the highest in patients with SNV within the first 3 months after diagnosis (adjusted IRR: 8.90 compared to TB ≥ 12 months). In Cox regression analysis, the diagnosis of microscopic polyangiitis [hazard ratio (HR) 3.22, 95% CI 1.04–9.99], granulomatosis with polyangiitis (HR 4.63, 95% CI 1.53–14.02), and polyarteritis nodosa (HR 3.51, 95% CI 1.13–10.88) were independent factors associated with TB. Conclusion: Even when considering the high incidence of TB in the geographic region, the risk of TB increased in patients with SNV, with a difference based on disease subtypes. Moreover, taking into account of the high incidence of TB in SNV, vigilant monitoring for TB is required especially during the early disease period.